Henry at Work : Thoreau on Making a Living - Kaag, John J., 1979-; Belle, Jonathan van (Book collections on Project MUSE., 2023)
"In this book, John Kaag and Jonathan van Belle illuminate an underexplored aspect of worked-over cultural icon Henry David Thoreau and what his thinking has to tell us about the way we work now. Henry at Work overturns the popular perception of Thoreau as a navel-gazing recluse, scornful of work and other mundanities. Just the opposite, they argue, Thoreau worked hard and thought intensely about work: why we do it, what we hope to gain from it, and what it does to us. They aim to show readers not only Thoreau the writer and philosopher, but also the lesser-known Thoreau: Thoreau the worker, economist, and even the efficiency expert"--